Research progress on the premature ovarian failure caused by cisplatin therapy - Li, Zelin; Qi, Haodong; Li, Zhengyang; Bao, Yuxuan; Yang, Kangping; Min, Qinghua (Frontiers in Oncology, 2023)
Cisplatin is a common anticancer drug able to kill tumor cells, but it causes adverse reactions in the kidney, digestive tract, and other systems. The antitumor effects of cisplatin are mainly due to its ability to bind to the DNA in tumor cells to prevent replication, thereby reducing RNA and protein syntheses, leading to cell damage and death. Cisplatin has a wide range of applications; it can be used to treat cervical, thyroid, ovarian, and other cancers. Cisplatin has a beneficial therapeutic effect, but its therapeutic selectivity is poor. In addition to eliminating diseased target cells, cisplatin can damage normal cells; in women of reproductive age being treated for cancer, cisplatin can lead to ovarian function impairment, premature ovarian failure (POF), and/or infertility. Therefore, reducing the adverse effects of cisplatin on ovarian function is an important topic in clinical research. In this paper, we explore the research progress on the POF caused by cisplatin treatment.